2008
DOI: 10.1177/000313480807400406
|View full text |Cite
|
Sign up to set email alerts
|

Perils of Rib Fractures

Abstract: Rib fractures (RF) are noted in 4 to 12 per cent of trauma admissions. To define RF risks at a Level 1 trauma center, investigators conducted a 10-year (1995–2004) retrospective analysis of all trauma patients. Blunt chest trauma was seen in 13 per cent (1,475/11,533) of patients and RF in 808 patients (55% blunt chest trauma, 7% blunt trauma). RF were observed in 26 per cent of children (<18 years), 56 per cent of adults (18–64 years), and 65 per cent of elderly patients (≥65 years). RF were caused by moto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
76
3
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 105 publications
(81 citation statements)
references
References 26 publications
1
76
3
1
Order By: Relevance
“…Rib fractures were present in 23% of our patients. Although rib fractures are relatively common, our percentage is lower than previous reports (35–50%) 7,9,14,15 . This is despite the high frequency of pedestrian (26%) and vehicle occupants (33%) in our study 2,6,8 …”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…Rib fractures were present in 23% of our patients. Although rib fractures are relatively common, our percentage is lower than previous reports (35–50%) 7,9,14,15 . This is despite the high frequency of pedestrian (26%) and vehicle occupants (33%) in our study 2,6,8 …”
Section: Discussioncontrasting
confidence: 75%
“…Penetrating injuries were rare in this population, with only six (4%) reported cases. Our results are lower than other series, 9,10,14 possibly because of stringent gun laws in Australia, and limited conflict and poverty when compared internationally 10,17 . Inci and colleagues 17 list the common injuries resulting from penetrating trauma as haemothorax and pneumothorax.…”
Section: Discussioncontrasting
confidence: 64%
“…Fractures of the lower ribs 9 to 12 can compromise the diaphragm, liver, spleen, kidneys, and adrenal glands, and it has also been suggested that laterally located rib fractures contribute to a higher risk of mortality, especially in patients aged over 45 years . Table outlines the relationship of the rib fracture location with visceral organ injury …”
Section: Discussionmentioning
confidence: 99%
“…Apart from being a nonfeasible imaging modality for claustrophobic patients, a limitation in its detection of rib fracture encompasses the possibility of a nondisplaced fracture being falsely diagnosed due to partial volume effects . Artefacts resulting from respiratory motion can also hinder the detection of rib fractures, especially those located in the anterior chest wall …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation